Houses, Secrets, and the Closet Locating Masculinities from the Gothic Novel to Henry James - Bauer, Gero (Lettre, 2016)
»Houses, Secrets, and the Closet« investigates the literary production of masculinities and their relation to secrets and sexualities in 18th and 19th century fiction. It focusses on close readings of Gothic fiction, Sensation Novels, and tales by Horace Walpole, Ann Radcliffe, William Godwin, Mary Elizabeth Braddon, Wilkie Collins, and Henry James. The study approaches these texts through the lens of domestic space, gender, knowledge, and power. This approach serves to investigate the cultural roots of the »closet« - the male homosexual secret - which reveals a more general notion of male secrecy in modern society. The study thus contributes to a better understanding of the cultural history of masculinities and sexualities.